Sosialisasi Dan Pelatihan Guru Membuat Buku Digital Cerita Bergambar Sebagai Pendukung Pembelajaran Literasi Siswa - Sutarini Sutarini; Hasanah Hasanah; Nirmawan Nirmawan; Divan Sinurat; Fathin Nazirah Aulia; Lesiana (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the capacity of teachers at the Al-Marwa Private Elementary School (MIS) in creating interactive and engaging digital literacy learning media, namely digital picture story books. The background to this activity is the low level of student literacy and the continued dominance of conventional learning methods that have not optimally utilized digital technology. Through a participatory training approach, teachers are equipped with digital literacy knowledge and technical skills using applications such as Canva and Heyzine to create digital books. The implementation results show that teachers experienced an increased understanding of digital literacy and enthusiasm in developing new learning media. Evaluations from 11 participants showed a high level of satisfaction with the material, understanding of digital literacy, and readiness to implement the training results. This activity not only strengthens teachers' competency in integrating technology into learning but also encourages the achievement of Key Performance Indicators (IKU) and the spirit of Independent Learning Independent Campus (MBKM) through collaboration between lecturers and students. It is hoped that this activity can be implemented sustainably, and the training model implemented has the potential to be replicated in other schools to support improving the quality of digital literacy-based education.